Introduction To Computer Science Using Java, Student Edition - Liberty Jesse (Glencoe--McGraw Hill, 2003)
Glencoe’s Introduction to Computer Science Using Java provides students with a highly visual way of learning Java programming. This colorful text provides the information needed for students enrolled in Computer Science I courses, and for students planning to take the AP Computer Science A exam (which has recently switched from C++ to Java). An AP correlation chart is provided in the student edition to help readers locate information that is relevant to the A exam, and “AP Exam Prep” exercises throughout the book help students prepare for the AP test. The Teacher Resource Manual also provides AP information and resources for teachers, and links to important AP sites can be found on the book’s Web site.